Consumo, sustentabilidade e origem: segmentação e estratégias para mercados locais de produtos da Amazônia - FERREIRA, Mariana Faro (Universidade Federal do Pará, 2024)
The Amazon is widely regarded as a realm of abundant possibilities within the context of the bioeconomy, owing to the vast size and diversity of its biocultural resources. However, scant attention has been paid to the consumption perspective concerning factors that could impact the development of local markets for products embodying the unique characteristics of the region. This research, grounded in the theoretical framework of marketing and consumer behavior studies, seeks to a) scrutinize elements linked to the concept of sustainable consumption and associated consumer behaviors; b) identify consumption patterns of the population of Belém city, Pará, Brazil; and c) propose market segmentation-based marketing strategies that contribute to the growth of local markets for Amazonian products. A literature review, employing Content Analysis (CA), revealed key elements of the sustainable consumption concept. These encompass the multidimensionality of the concept, encompassing social and environmental aspects alongside economic considerations; its robust association with the notion of Sustainable Development, thereby affording it a broad scope easily embraced as discourse by diverse sectors, yet posing challenges in guiding production and consumption practices. To guide practices, we consider that operational definitions must include: a) emphasis on multiple dimensions (social, environmental and economic), b) scope of product and processes, c) inclusion of production and consumption impacts and e) indication of the levels of action considered (whether individual, collective or public/governmental). Findings from a survey involving a probabilistic sample of the population in Belém (PA) indicated that consumers in the capital prioritize functionalities, fragrance, price, and ingredients as their primary criteria when selecting shampoos. Concerning origin, both generally and specifically in local production within the Amazon, this was not deemed a significant attribute by any of the demographic profiles in the studied population. Strategies for Amazon-based businesses were subsequently proposed based on the discussed results, encompassing all four levels of the marketing mix (product, place, promotion, and price). These strategies incorporate elements for differentiation based on origin, capitalizing on the region's unique features for product development, and acknowledging the idiosyncrasies of three distinct segments of Pará state consumers. In summary, a focus is suggested on: a) the development of products oriented to local demand; b) differentiation by origin; c) increased availability; and d) positioning by quality. In a scenario of growing interest in the bioeconomy, the development of marketing strategies aimed at the sustainable consumption of products originating in the Amazon will still face broad concepts and lack of knowledge about the behavior of local consumers, difficulties that can be overcome by focusing on product attributes, greater information about consumption and economic and cultural valorization of its socio-biodiversity.